Réponses

2013-06-21T11:05:02+02:00

17/3 × 2/7 = (17 × 2)/(3 × 7) = 34/21

 

13/3 + 2/7 = (13 × 7)/(3×7) + (2 × 3)/(7 × 3) = 91/21 + 6/21 = (91 + 6)/21 = 97/21

 

(7/5 + 4/9) × 2/3 = ((7 × 9)/(5 × 9) + (4 × 5)/(9 × 5)) × 2/3 = (63/45 + 20/45) × 2/3 = ((63 + 20)/45) × 2/3 = 83/45 × 2/3 = (83 × 2)/(45 × 3) = 166/135

 

(16/5 - 3/4) × (17/5 - 11/7) = (64/20 - 15/20) × (119/35 - 55/35) = 49/20 × 64/35 = 7/20 × 64/5 = 7/5 × 16/5 = 112/25

 

(16/5 - 3/4) + (17/5 - 11/7) = 49/20 + 64/35 = 343/140 + 256/140 = 599/140

 

V(2) + 3V(2) = (1 + 3)V(2) = 4V2

 

V(2) × V(5) = V(2 × 5) = V(10)

 

V(2) + V(8) = V(2) + V(4 × 2) = V(2) + V(4) × V(2) = V(2) + 2 × V(2) = (1 + 2) × V(2) = 3V(2)

 

 

(3/16)/(5/4) = 3/16 × 4/5 = 3/4 × 1/5 = 3/20

 

(3 × 10⁻² × 5 × 10⁵)/(6 × 10³ × 7 × 10⁻¹) = (1 × 5 × 10⁻²⁺⁵)/2 × 7 × 10³⁻¹) = (5 × 10³)/(14 × 10²) = 5/14 × 10³⁻² = 5/14 × 10 = 50/14 = 25/7